Diversity and Biological Control Potential of Haloalkaliphilic Fungi from Lake Magadi, Kenya - Orwa, Philemon (University of Embu, 2020)
Fungi are eukaryotic microorganisms that have simple multicellular or unicellular cell structures. They are distributed in terrestrial soils, forests, aquatic habitats and in extreme environments with high ambient salts, temperature, pH and pressure. Fungi from extreme environments are potential sources of novel biocatalysts for example antimicrobial agents that can help solve the rising cases of drug resistance. However, the diversity of fungi recovered and described from less studied environments such as the soda lakes is quite low as compared to the soil ecosystem. Very few haloalkaliphic fungi have been recovered from hypersaline environments. In this study, we explored the cultivable fungal diversity in Lake Magadi and their ability to produce secondary metabolites. Dilution plate technique was used to isolate fungi from soda lake soils using alkaline media (Potato dextrose agar, Malt extract agar, Oatmeal agar and Sabouraud dextrose agar) prepared using sterilized lake water from the lake. Unique isolates were selected based on morphological features and subjected to physiological tests to determine their ability to grow at different pH, temperature and salts ranges. Molecular characterization was done by analysis (BLAST) of the amplified conserved regions of 18SrDNA followed by phylogeny. Ability of the isolates to utilize different carbon sources was tested on media supplemented with different substrates (starch, cellulose, casein, lignin, pectin, xanthan, chitin, Tween 20). Antimicrobial screening was done using both crude and cell free extracts to determine the ability of the isolates to produce metabolites (comparison of mean diameter of inhibition zones) that can be used to control both human pathogens and agricultural pathogens. The test pathogens included human pathogens Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Salmonella spp., Shigella spp. and Candida albicans which were laboratory isolates and plant pathogens Epicoccum sorghinum strain JME-11, Alternaria tenuissima, Didymella glomerata, Schizophyllum commune isolate ScGD28, Phoma destructiva, Cladosporium halotolerans CBS 119416, Aspergillus fumigatus EG11-4 and Dickeya dianthicola (field isolates). In total, 52 isolates were recovered from the study having different pigmentations. Their physiology depicted actual characteristic of haloalkaliphilic environments as the fungi tolerated extreme pH of up to 10 and salts (15-20%) and some grew at 35-40ºC. Sequence analysis indicated that the isolates were affiliated to 18 different genera with Aspergillus, Penicillium, Phoma, Cladosporium, and Acremonium. Substrate utilization tests showed that the different isolates produced proteases, chitinases, cellulases, amylases, pectinases and lipases. Isolates 2M, 59M, 69M, 87M, 100M, 111M and 113M were outstanding as they produced more than four enzymes. Results from the antimicrobial screening showed one isolate (11M from Site 3 soil) with 99% affiliation to Penicillium chrysogenum CBS 306.48 was able to inhibit major enteric bacteria and plant pathogenic fungi. Similar studies on saline environments have reported the phylum Ascomycota as the dominant fungal group and all the genera recovered in this study are classified in the same phylum. Antimicrobial from the fungal isolates provide a basis for pharmacological research since they can further be purified to obtain compounds that can be used as antibiotics or biopesticide against human and plant pathogens respectively. This can provide a solution to the rising problem of antibiotic resistance and pesticide resistance.
Masters Thesis